RBP-J imposes a requirement for ITAM-mediated costimulation of osteoclastogenesis - Li, Susan (J Clin Invest, 2014)
Osteoclastogenesis requires activation of RANK signaling as well as costimulatory signals from immunoreceptor tyrosine-based activation motif-containing (ITAM-containing) receptors/adaptors, predominantly tyrosine kinase–binding proteins DAP12 and FcRγ, in osteoclast precursors. It is not well understood how costimulatory signals are regulated and integrated with RANK signaling. Here, we found that osteopetrotic bone phenotypes in mice lacking DAP12 or DAP12 and FcRγ are mediated by the transcription factor RBP-J, as deletion of Rbpj in these mice substantially rescued the defects of bone remodeling. Using a TNF-α–induced model of inflammatory bone resorption, we determined that RBP-J deficiency enables TNF-α to induce osteoclast formation and bone resorption in DAP12-deficient animals. Thus, RBP-J imposes a requirement for ITAM-mediated costimulation of RANKL or TNF-α–induced osteoclastogenesis. Mechanistically, RBP-J suppressed induction of key osteoclastogenic factors NFATc1, BLIMP1, and c-FOS by inhibiting ITAM-mediated expression and function of PLCγ2 and activation of downstream calcium-CaMKK/PYK2 signaling. Moreover, RBP-J suppressed Plcg2 expression and downstream calcium oscillations indirectly by a TGF-β/PLCγ2/calcium axis. Together, our findings indicate that RBP-J suppresses ITAM-mediated costimulation, thereby limiting crosstalk between ITAM and RANK/TNFR signaling and allowing fine tuning of osteoclastogenesis during bone homeostasis and under inflammatory conditions. Furthermore, these data suggest that environmental cues that regulate RBP-J expression/function potentially modulate the requirement for costimulatory signaling for osteoclast differentiation and bone remodeling.